The Task of Interlingual Adaptation in Translation Strategies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the task of interlingual adaptation within the framework of translation strategies. It examines the theoretical foundations of adaptation, the challenges translators encounter, and the methods employed to address these challenges. By analyzing practical examples and case studies, the study aims to shed light on the importance of interlingual adaptation as a fundamental component of effective translation and its implications for intercultural communication in a globalized world.